2019
DOI: 10.35940/ijitee.l2529.1081219
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Process of Obtaining Organo-Mineral Fertilizer Based on Nitrogen Acid Decomposition of Non-Conditional Phosphorites of Central Kyzylkumes and Poultry Cultivation Waste

Abstract: The article presents the results of decomposition of substandard phosphorites at a non-full rate of nitric acid (10-50% of stoichiometry on CaO), followed by its processing by bird droppings in various ratios. The optimal parameters for obtaining organic mineral fertilizers are determined, the technological scheme is given and the material balance is calculated, the possibility of obtaining nitrogen-phosphorus-humus fertilizers based on substandard phosphorites and bird droppings is shown, by composition (wt.%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The purpose of this study is to obtain an organomineral fertilizer based on cattle manure and phosphorites of the Central Kyzylkum. In contrast to works [13][14][15], phosphorites were activated by neutralizing the waste water of the oil and fat industry.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The purpose of this study is to obtain an organomineral fertilizer based on cattle manure and phosphorites of the Central Kyzylkum. In contrast to works [13][14][15], phosphorites were activated by neutralizing the waste water of the oil and fat industry.…”
Section: Introductionmentioning
confidence: 94%
“…The use of organic and organomineral fertilizers makes it possible to mobilize soil phosphates by converting the phosphorus present in them into a mobile state [12]. In this area, a number of studies have been carried out on obtaining organomineral fertilizers based on composting of phosphorites of the Central Kyzylkum with livestock manure and poultry manure [13][14][15]. These studies have shown that phosphorus in phosphorites is converted into a plant-assimilable form under the action of humic acids, which are formed during composting.…”
Section: Introductionmentioning
confidence: 99%